Analisis Hidrograf Debit Banjir Rancangan Daerah Irigasi Danau Tampang - Ratih Baniva; Andre Wibowo (Jurnal Konstruksi, 2026)
The Tampang Lake Irrigation Area, located in Muara Enim Regency, South Sumatra Province, is a wetland region that is highly susceptible to flooding due to high rainfall intensity and relatively flat topography. This study aims to analyze the design flood hydrograph of the Lingkis River using the HEC-HMS hydrologic modeling software. The novelty of this study lies in the integration of rainfall analysis, Intensity–Duration–Frequency (IDF) curve analysis, the Alternating Block Method (ABM), and HEC-HMS simulation for a wetland irrigation area that has received limited attention in previous studies, particularly within the Tampang Lake Irrigation Area. The research methodology involved simulating flood hydrographs using HEC-HMS, with the simulation results serving as the basis for estimating the design flood discharge. The analysis indicates that the highest rainfall intensity occurred at a 10-minute duration with a 10-year return period, reaching 126.80 millimeters per hour. The HEC-HMS simulation produced peak flood discharges of 176.7 cubic meters per second with a runoff volume of 40.05 millimeters for the 2-year return period, 234.7 cubic meters per second with a runoff volume of 52.88 millimeters for the 5-year return period, and 274.1 cubic meters per second with a runoff volume of 61.56 millimeters for the 10-year return period. The findings of this study are expected to contribute to the provision of reliable design flood discharge data to support the planning of wetland irrigation systems and flood mitigation efforts in the Tampang Lake Irrigation Area.